The efficacy of unitary and polynomic models of standardisation in minority language contexts: Ideological, pragmatic and pedagogical issues in the standardisation of Irish - O Murchadha, Noel (My University, 2016)
Although traditional, unitary models of language standardisation have been prominent in minority languages, it is contended that this approach reproduces dominant language hierarchies and hegemonies, diminishes linguistic diversity and marginalises speakers who do not conform to prestige models. The polynomic model has been described as an alternative that is possibly more efficacious in minority language maintenance, revitalisation and revival. Focusing on the codification of written Irish, this article assesses the efficacy of unitary and polynomic models of codification. The Irish context offers a rich locus for the study of these issues, owing to the long-standing presence there of conflicting ideologies of uniformity and plurality with regard to codification of the written variety. These conflicting orientations are manifest in the development of the 1958 unitary written standard, in a recent review of this standard for writing, and in the rejection of this review in favour of a more unitary model. The article demonstrates that many ideological, pragmatic, pedagogical and political obstacles inhibit the effectiveness of standardisation efforts in minority language situations, whether efforts are based on unitary or polynomic principles.
PUBLISHED
Keywords: Irish language; Gaeilge; Minority languages; Bilingualism; Sociolinguistics; Language revitalisation; Language shift; Language vitality; Identities in Transformation; Applied Linguistics; Celtic Linguistics; Folk Linguistics; Linguistics; SOCIOLINGUISTICS